Kolaborasi Pemasaran Digital Menggunakan Media Sosial dan Marketplace untuk Meningkatkan Produktivitas UMKM - Fetty Tri Anggraeny; Dedin F. Rosida; Wahyu S.J. Saputra; Handoyo Prasetyo (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Digital marketing is currently growing rapidly. The COVID-19 pandemic has increasingly triggered the acceleration of digital marketing, especially for SME (Small and Medium Entreprise). The growth of social media users and marketplace users both as buyers and sellers has also soared. Today's society is starting to shift to cashless transactions. Both social media and marketplace have advantages that can be collaborated as digital marketing. Social media with diverse users and a marketplace that offers easy online store management and promo programs. The collaboration of these 2 digital tools is able to increase the productivity of UMKM